The Development Application Promote Agritourism of Pakdee Farm with Augmented Reality Technology - Sampaothong, Tirawat; Sanchana, Wiraiwan (Journal of Applied Informatics and Technology, 2023)
This research is a development of an application on the Android operating system. Its purposes are 1) to development application promote agritourism of Pakdee Farm with augmented reality technology and 2) to study the tourists’ satisfaction with this application with application promote agritourism of Pakdee Farm with augmented reality technology. The programs used to develop the application consisted of the Unity Program and the C# Program. Design 3D models deer model with Blender program and Google's ARCore software to develop the augmented reality technology. The research sample consisted of 50 tourists visiting Pakdee Farm. The data collecting instrument was a questionnaire to assess satisfaction. It comprised three aspects: the content, the design and formatting, and the benefits of the application. The data were analyzed using the mean and standard deviation. The results of the study show that (1) when using the application, the users have to scan the space by phone camera and then the program will find space to create 3D models with augmented reality technology; and (2) regarding the users’ satisfaction, it is found that the overall level of the users’ satisfaction with the application promote agritourism of Pakdee Farm with augmented reality technology is high.